Extracellular Vesicles and Transforming Growth Factor β Signaling in Cancer - Rodrigues-Junior, Dorival Mendes; Tsirigoti, Chrysoula; Lim, Sai Kiang; Heldin, Carl-Henrik; Moustakas, Aristidis (Frontiers in Cell and Developmental Biology, 2022)
Complexity in mechanisms that drive cancer development and progression is exemplified by the transforming growth factor β (TGF-β) signaling pathway, which suppresses early-stage hyperplasia, yet assists aggressive tumors to achieve metastasis. Of note, several molecules, including mRNAs, non-coding RNAs, and proteins known to be associated with the TGF-β pathway have been reported as constituents in the cargo of extracellular vesicles (EVs). EVs are secreted vesicles delimited by a lipid bilayer and play critical functions in intercellular communication, including regulation of the tumor microenvironment and cancer development. Thus, this review aims at summarizing the impact of EVs on TGF-β signaling by focusing on mechanisms by which EV cargo can influence tumorigenesis, metastatic spread, immune evasion and response to anti-cancer treatment. Moreover, we emphasize the potential of TGF-β-related molecules present in circulating EVs as useful biomarkers of prognosis, diagnosis, and prediction of response to treatment in cancer patients.